Особенности распределения напряжений в хвостовых соединениях рабочих лопаток паровых турбин - Сухинин, В. П.; Фурсова, Т. Н. (НТУ "ХПИ", 2008)
У роботі розглядається розподіл напруг для хвостового з’єднання грибоподібного типу в об’єму конструкції при різних варіантах контакту по опорних площинах за допомогою експериментального методу фотопружності. Запропоновані способи поліпшення розподілу напруг за рахунок вибору оптимальних форм опорних площин.

In work, distributing of tensions is examined for tail connection of mushroom-like type in the volume of construction at the different variants of contact on supporting grounds by the experimental method of photoelasticity. The methods of improvement of distributing of tensions are offered due to the choice of optimum forms of supporting grounds.
Features of distributing of tensions are in tail connections of workings shoulder-blades of steam turbines
Keywords: напряженно-деформированное состояние; статическое растяжение; экстремальные нагрузки; метод фотоупругости